Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Microplastics in two fish species from Prydz Bay and King George Island: Occurrence, characteristics and risk assessment - Kexin Zhang; Zhiwei Gao; Peng Ju; Yunmei Sun; Jie Zhang; Yan Gu; Chengjun Sun; Haitao Ding (Marine Pollution Bulletin, 2026)

A unified density-aware network for stored-grain pest detection with intelligent risk assessment - Long Chen; Rui Li; Chengjun Xie; Peng Chen; Jie Zhang; Jianming Du; Hongbo Chen; Runsheng Qi; Jiahui Sun (Journal of Stored Products Research, 2026)

Mitochondria-targeted nanoformulation inhibits periodontal ligament stem cells pyroptosis to promote periodontal tissue regeneration in periodontitis - Xinyuan Shao; Yuxiao Wang; Guichun Wang; Jingjing Hu; Yu Cheng; Chaoqi Wei; Zixuan Shu; Chengjun Peng; Yang Ding; Jian Guo; Zhifei Cheng; Shuangying Gui (Chemical Engineering Journal, 2025)

Coseismic surface deformation and source mechanism of the 2023 Ms 6.2 Jishishan earthquake, northeastern Tibetan Plateau - Peng Chen; Siqi Shu; Zhonghai Wu; Tao Wang; Chengjun Feng; Jiamei Liu; Shuai Zhang; Haojie Wang; Kun Li (Journal of Structural Geology, 2024)

CCL2-scavenging nanodecoy hydrogel multi-step remodel monocytes recruitment and macrophages polarization for periodontitis treatment - Yuxiao Wang; Guichun Wang; Jiaxin Li; Maomao Tang; Baoqing Jia; Zixuan Shu; Yang Ding; Chengjun Peng; Shuangying Gui; Jian Guo (Chemical Engineering Journal, 2024)

Effects of polypropylene films and leached dissolved organic matters on bacterial community structure in mangrove sediments - Jiatong Li; Xue Li; Jiwei Luo; Peng Huang; Chengjun Ge; Xing Yang; Hailong Wang (Science of The Total Environment, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Occurrence of microplastics in the Haima cold seep area of the South China Sea - Di Zhang; Jingxi Li; Peng Ju; Wei Cao; Fenghua Jiang; Chengjun Sun (Science of The Total Environment, 2024)

A novel photoelectrochemical self-screening aptamer biosensor based on CAU-17-derived Bi2WO6/Bi2S3 for rapid detection of quorum sensing signal molecules - Shiliang Wang; Peng Ju; Weixing Liu; Jingtian Chi; Tiantong Jiang; Zhe Chi; Shuai Wang; Ri Qiu; Chengjun Sun (Analytica Chimica Acta, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

A new hydrological climatic proxy in arid lake sediments: Iodine‑uranium concentrations - Xue Zhao; Xiaolin Hou; Zhao Huang; Chengjun Zhang; Peng Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Trash to treasure: Green synthesis of novel Ag2O/Ag2CO3 Z-scheme heterojunctions with highly efficient photocatalytic activities derived from waste mussel shells - Jiazhen Cao; Peng Ju; Zheyang Chen; Kunpeng Dou; Jingxi Li; Peng Zhang; Zuhao Zhu; Chengjun Sun (Chemical Engineering Journal, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

Dynamic response of the inhomogeneous pavement structure containing a buried fault zone under the moving aircraft loads - Jiawei Wan; Bin Li; Yang Gao; Chengxuan Tan; Chengjun Feng; Peng Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Nutritional Profile and Bioremediation of Tropical Marine Aquaculture with an Integrated Microalgae and Bacteria Symbiosis - Ruiyang Ma; Shiyu Xie; Huiting Jia; Linhai Pu; Licheng Peng; Chengjun Ge (Water, Air, & Soil Pollution, 2022)

Combined Effects of Microplastics and Benzo[a]pyrene on the Marine Diatom Chaetoceros muelleri - Yuanyuan Su; Huaiyuan Qi; Yipeng Hou; Mengyi Gao; Jie Li; Minggang Cai; Xiaoshan Zhu; Miao Chen; Chengjun Ge; Dongdong Fu; Zezheng Wang; Licheng Peng (Frontiers in Marine Science, 2022)
Microplastics are regarded as ubiquitous pollutants in the ocean and have attracted worldwide concerns. Benzo[a]pyrene (B[a]P), one of typical polycyclic aromatic hydrocarbons (PAHs), is commonly detected in marine environment. Once coexisted, the microplastics and B[a]P may interact with each other and result in combined toxicity to organisms, and these remain to be systematically elucidated. Thus, this study aims to investigate (i) the effects of single micro-sized polystyrene (mPS), polyethylene terephthalate (mPET), and B[a]P on cell growth of Chaetoceros muelleri ; and (ii) the interaction of microplastics and B[a]P, and their combined effects on C. muelleri . The results showed that both single microplastics and B[a]P at a high concentration of 150 μg/L inhibited the growth of C. muelleri . For single treatment of microplastics, stronger inhibition effects on microalgae was caused by mPET than that of mPS, with the highest IR of 25.23 and 11.17%, respectively. This may be attributed to the obvious surface roughness of mPET. By comparison, the combined effects of microplastics and B[a]P significantly inhibited the growth of C. muelleri as compared with the single treatment of B[a]P ( P < 0.05). Synergistic effect was found in the combination of microplastics with B[a]P at high concentrations of 150 μg/L. Interestingly, the antagonistic effect on C. muelleri was observed in the combined treatment of microplastics and B[a]P at low concentrations of 10 μg/L. In addition, the pollutants reduced the content of photosynthetic pigments in microalgal cells. The SOD and MDA content of microalgae increased in the early stage of exposure to pollutants (e.g., Days 1 and 5), but decreased in the later stage (Day 15) compared with the control group. The decreased superoxide dismutase (SOD) and catalase (CAT) activity in single and composite systems may indicate that the antioxidative enzymatic system of microalgae has been inhibited or destroyed. This study will be helpful to further explore the ecological threats of microplastics and PAHs to the marine ecosystem.

New insights into the toxic interactions of polyvinyl chloride microplastics with bovine serum albumin - Peng Ju; Yu Zhang; Jinfeng Ding; Yifan Zheng; Shuai Wang; Fenghua Jiang; Chengjun Sun (Environmental Science and Pollution Research, 2021)

The effective removal of phenol from aqueous solution via adsorption on CS/β-CD/CTA multicomponent adsorbent and its application for COD degradation of drilling wastewater - Hong Peng; Changjun Zou; Chengjun Wang; Wenyue Tang; Juxian Zhou (Environmental Science and Pollution Research, 2020)

Characteristics and main causes of earth fissures in northeastern Beijing Plain, China - Jiawei Wan; Bin Li; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi (Bulletin of Engineering Geology and the Environment, 2020)

Degradation of lipids in seasonal hypoxic seawater under different oxygen saturation - Yunhong He; Chengjun Sun; Wenjuan Li; Gui-Peng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2018)

Effects of red mud addition on cadmium accumulation in cole (Brassica campestris L.) under high fertilization conditions - Peng Li; Xianjia Peng; Zhaokun Luan; Tongke Zhao; Chengjun Zhang; Baocun Liu (Journal of Soils and Sediments, 2016)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Co-seismic and post-seismic effects of the Tohoku-Oki M W 9.0 earthquake in North and Northeast China - Chengjun Feng; Peng Zhang; Chengxuan Tan; Bangshen Qi; Lianjie Wang (Journal of Seismology, 2016)

The stress state of the Beichuan-Jiangyou segment of the Longmenshan fault before and after the Wenchuan M S 8.0 Earthquake - Chengjun Feng; Qunce Chen; Chengxuan Tan; Xianghui Qin; Peng Zhang; Wen Meng (Journal of Earth Science, 2014)